2021
DOI: 10.2478/orga-2021-0010
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Internal Knowledge Sharing on Sales Department’s Innovativeness and New Product Commercialization

Abstract: Background and Purpose: Innovativeness and new product commercialization are highly important for companies. Therefore, a deep understanding of the impact of all potentially influential drivers of success is critical. The purpose of the paper is to explore the impact of internal knowledge sharing on new product selling and sales innovativeness as well as the impact of empowerment on internal knowledge sharing and, indirectly, on new product selling and sales innovativeness. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 47 publications
(55 reference statements)
1
3
0
Order By: Relevance
“…The results found in the study initially allowed us to conclude that the model is adequate to investigate the phenomenon because in addition to meeting the validity and reliability criteria required for the use of SEM, a relatively high value was obtained to explain innovativeness (R 2 = 0.716) in the electronics industry. Another result that supports this statement is that a positive and significant relationship was found between innovativeness and innovation performance in this industry (H3), which is well understood in the literature (Anning-Dorson & Nyamekye, 2020;Baierle et al, 2018;Brettel et al, 2015;Oliveira et al, 2018;Ruži c & Benazi c, 2021;Santos-Vijande et al, 2021), and the positive relationship was also confirmed empirically in this study.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The results found in the study initially allowed us to conclude that the model is adequate to investigate the phenomenon because in addition to meeting the validity and reliability criteria required for the use of SEM, a relatively high value was obtained to explain innovativeness (R 2 = 0.716) in the electronics industry. Another result that supports this statement is that a positive and significant relationship was found between innovativeness and innovation performance in this industry (H3), which is well understood in the literature (Anning-Dorson & Nyamekye, 2020;Baierle et al, 2018;Brettel et al, 2015;Oliveira et al, 2018;Ruži c & Benazi c, 2021;Santos-Vijande et al, 2021), and the positive relationship was also confirmed empirically in this study.…”
Section: Discussionsupporting
confidence: 88%
“…According to Baierle et al (2018), one innovation variable may influence more than one construct of competitiveness. Other studies have corroborated this argument, such as Kyrgidou and Spyropoulou (2013), Oliveira et al (2018), Zhang et al (2020) and Ružić and Benazić (2021), and have emphasized that innovativeness in organizations has attracted considerable attention in the literature and that existing knowledge is limited in relation to its drivers and their simultaneous effects as well as the impacts on innovation performance.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Firstly, enterprises need to attach importance to enterprise knowledge acquisition, not only because knowledge acquisition is conducive to integrating the existing knowledge of enterprises and improving sustainable innovation performance, but also because enterprise knowledge helps to build organizational resilience of enterprises and promote enterprise innovation. Based on this, on the one hand, enterprises should not only attach importance to internal knowledge sharing activities [85], increase resource investment, and reduce process-oriented blockage to form efficient knowledge flow, but also improve internal R&D investment [86], make full use of existing internal innovation knowledge, and convert innovation resources into output as soon as possible. On the other hand, enterprises should communicate with external stakeholders or industry-academia-research institutions to acquire external knowledge, consider high-frequency and in-depth interaction with external knowledge acquisition channels on the basis of measuring their own capabilities and costs, and establish deep relationships to obtain more valuable knowledge resources.…”
Section: Practical Implicationsmentioning
confidence: 99%